Three, Now Forgotten, Nineteenth-Century Leiden Scholars - Bearman, Peri (Die Welt des Islams, 2026)
When a field is in its genesis, as the study of Islam was in the nineteenth century, with so much still to be discovered and published, the loss of a promising star hits hard. This brief essay is written in homage to three up-and-coming Dutch scholars of the mid-nineteenth century, Hendrik Engelinus Weyers, J. J. B. Gaal, and Willem H. Engelmann, all from Leiden University, who were struck down in their prime. As their names have been now mostly erased in history, this article honors their all too short lives and work.